-11-3(2*-11-7)=

Simple and best practice solution for -11-3(2*-11-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11-3(2*-11-7)= equation:


Simplifying
-11 + -3(2 * -11 + -7) = 0

Multiply 2 * -11
-11 + -3(-22 + -7) = 0

Combine like terms: -22 + -7 = -29
-11 + -3(-29) = 0

Multiply -3 * -29
-11 + 87 = 0

Combine like terms: -11 + 87 = 76
76 = 0

Solving
76 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 2(2x-9)-5=2(x-5)-3 | | 25-12x=30 | | 7x-(2x+17)=18 | | 49=7/8(v) | | -7=-5a-2a | | 2x+11=-9x-18 | | 9(z-6)=4(z-4) | | 9(x+5)=9(x+10) | | t=3+14t-5t^2 | | h(t)=3+14t-5t^2 | | -2x+2=-1 | | 5s+2=5c-2 | | -5n+3=-22 | | 2x+13=-3x-20 | | -1/5x=-12 | | 5t-4=-14 | | (x*2)-9=x | | 8x+12=-6x-18 | | -6(m-23)=1 | | a+b=cfindb | | 8+5v=-8(-8v+8)+v | | 1/7-11=1/4x-14 | | 3.2+2.2x=3x | | x(2x-3)(4x+1)=0 | | 2x^2-2=45 | | -x-4.7=9 | | x/4=4/3 | | c=37+22h | | 12x-y=-10 | | 1/2r=3 | | c=22h+37 | | -36-8n=-3(3n+2)-5n |

Equations solver categories